Factors influencing TVET readiness among students at public secondary school: exploring interest, motivation, and self-efficacy - Nordin, Dg Nurulsyakirah; Omar, Muhd Khaizer (Association for Researcher of Skills and Vocational Training, 2024)
Technical and Vocational Education and Training (TVET) serves as an academic field for equipping students with necessary skills, providing them with practical and valuable workforce skills to navigate the challenges of the fourth industrial revolution. TVET adopts a dual teaching approach that encompasses general education, technological knowledge, and industry-specific training, serving as a primal tool in cultivating a workforce competence in the demands of the future. However, a concerning trend emerges as a deficiency in students pursuing TVET as mainstream education could lead to a decline in the skilled workforce for the country. This condition subsequently impacting the human capital development and skilled workforce across economic sectors.Hence, the current study seeks to understand the relationship between interest, motivation, and self-efficacy of secondary school students enrolled in general education programs and their readiness to advance their studies in TVET stream. Employing a quantitative research design, the study utilizes a survey method with a set of questionnaires. Three public secondary schools, are included in the research, comprising a total of 273 students. The sampling method employed is stratified random sampling. The findings of the study reveal that the interest, motivation, and self-efficacy levels of students, as well as their readiness to pursue further studies in TVET are notably high. Furthermore, a positive correlation is identified between interest, motivation, and self-efficacy, underscoring their influence on the preparedness of students to continue their education in TVET.